PERLINDUNGAN HUKUM TERHADAP INVESTOR SEBAGAI KONSUMEN DARI KEJAHATAN PENIPUAN INVESTASI ONLINE MENURUT UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Bakti Firmansyah (Iustitia Omnibus (Jurnal Ilmu Hukum), 2022)
Electronic transaction is a term used for every legal action carried out using a computer, computer network, and/or other electronic media. Investor is the same as the definition of consumer as referred to in UUPK. One of the important aspects in the protection of victims is the recovery or compensation provided to victims through the UUPK. From several cases that have occurred, it shows that in previous decisions the court through the panel of judges has so far been deemed less concerned about the rights of victims and more likely to take a safe position by implementing the status quo without thinking about making changes. Therefore, in the future the UUPK can be used as one of the laws and regulations that can ensnare perpetrators of investment crimes and provide legal protection for victims and the right to obtain compensation or compensation even without submitting a request or amalgamation of cases.